Sanut, Wayawaya, and the Naimbag a Biag in Ilokano Philosophy - Agcaoili, Aurelio S. (Budhi: a Journal of Ideas and Culture, 2019)
The essay articulates the fundamental connection of some of the basic concepts in Ilokano ethos as lived in the everyday in order to understand the basic contradictions of the Ilokano way of being in the world (Ilokano ontology), of being in a society marked by good intentions but evil practices. The notion of the good life as a political concept is explored, and its connection to knowledge (Ilokano epistemology) and freedom is established.